Palynology of some species of Passifloraceae Neotropical: Palynology of some Passifloraceae (Revista de Investigaciones Universidad del Quindío, 2011)
Pollen, as a highly conserved genetic element, is essential in the recognition of a taxon. Therefore, diversity of some species of Passiflora has been studied by using palynological characterization; hence, its importance is known as a tool to elicit the taxonomic controversy of the genus. Consequently, 30 samples of pollen were taken and analyzed under optical microscopy (acetolysis) and scanning electron microscopy SEM representing 20 species of Passiflora. It was included the species of the genus, P. incarnata, and P. macrophylla (the only species of subgenus Astrophea presenting monopodial branching).
Keywords: genus Passiflora; pollen; acetolysis; SEM